The Influence Of Instagram Social Media And Product Attraction On Interest To Buy Mieso Products At Mieso Store Btn High Click City - Jopinus Saragih; Hendri Mayanta Tarigan (International Journal of Artificial Intelligence Research, 2022)
This study aims to find out how The Influence Of Instagram Social Media And Product Attractiveness On Buying Interest In MSME Products, Warung Mieso Btn, Tebing Tinggi City. The results show thatiin the T (Partial) iI hypothesis test it can be seen that tcount (8.488) > ttable (1.661), and the significance value iis i0.00 < i0.05, it can be concluded that the first hypothesis of Social Media (X1) has a ipositive effect and significant to Purchase Interest (Y). The conclusion is that social media is very iuseful in product marketing, especially BTN miso where in addition to displaying various activities and products, social media plays a very important role in helping direct promotion. This research is in accordance with Farid Rusdi's 2020 research. The Effect of Attractiveness to Advertising on Social Media Instagram on Consumer Buying Interest (Survey of Brodo Shoe Products in West Jakarta Young People) where social media has a significant influence on buying interest. In the T (Partial) hypothesis test II, it can be seen ithat tcount (0.523) < ttable (1.661), and ithe significance value is 0.603 > 0.05, it means that ithe second hypothesis, namely the Product Attractiveness variable (X2) has no significant effect on Purchase Interest ( iY). The conclusion is that attractiveness has not been able to increase consumer buying interest, where the attraction iof products has already been offered by adding various additions to their products and this is not in accordance with Rusdi's 2020 research. Survey of Brodo Shoe Products among Young People in West Jakarta) where attractiveness plays an important role in promotion on social media. ithe third hypothesis can be seen that Fcount (22.652) > Ftable (2.70), and a significance value of 0.00 <0.05, it can be concluded that the third hypothesis is accepted, meaning that Social Media Variables (X1), Attractiveness Variables (X2) significant effect simultaneously (simultaneously) on the Purchase Interest Variable (Y)